Surface-Functionalized Nanocelluloses as Viscosity-Modifying Agents in Engineered Cementitious Composites - Liang, Long; Yang, Junlei; Lv, Guowei; Lei, Zhen; Li, Xiurong; Liu, Qiaoling (Frontiers in Materials, 2021)
This study investigated the feasibility of using nanofibrilliated celluloses (CNF) (0.1% by weight of binder materials) with three oxidation degrees, no oxidation (NCNF), low oxidation (LCNF), and high oxidation (HCNF), as a viscosity modifying agent (VMA) to develop polyethylene fibers (PE)-engineered cementitious composites (ECC). Attenuated total reflection-Fourier transform infrared (ATR-FTIR), dynamic light scattering (DLS), zeta potential were performed to characterize the properties of CNF with different oxidation degrees. More stable CNF suspensions could be obtained due to the increasing oxidation degree. Rheology tests showed that CNF replacing VMA could modify the plastic viscosity and yield stress of the fresh matrices. With increasing the oxidation degree of CNF, a significant enhancement was seen for the rheological parameters. It was conducted that CNF could increase the compressive strength, the tensile stress, the nominal flexural strength, and the fracture toughness compared with ECC using VMA, and much higher oxidation degrees yielded higher enhancements (HCNF ＞ LCNF ＞ NCNF). ECC using CNF to replace VMA also achieved ultra-high ductility behavior with the tensile strain of over 8% and the saturated multiple cracking pattern. These finds were supplemented by thermal gravimetric analysis (TGA), which showed that the degree of hydration increased with increasing the CNF surface oxidation degree. Additionally, the morphology images of PE fibers were observed by scanning electron microscope (SEM).